Sulphur Ylide Initiated Photopolymerization of Methyl Methacrylate - Mishra, A.; Mathur, G.N. (Asian Journal of Chemistry, 2010)
Solution polymerization of methyl methacrylate was carried out in the presence of visible light (440 nm) using 3-nitrophenacyl dimethyl sulfonium ylide as a photoinitiator at 30ºC. The initiator and monomer exponent values were calculated to be 0.49 and 1.0 respectively. An average value of Kp2/KT was 2.0 x 10–2. The polymerization was restarted in the presence of benzoquinone. Kinetic data and ESR studies indicate that the overall polymerization takes place by radical mechanism.